2011
DOI: 10.1111/j.1365-2958.2011.07646.x
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli replication inhibitor CspD is subject to growth‐regulated degradation by the Lon protease

Abstract: SummaryPost-translational proteolysis-dependent regulation of critical cellular processes is a common feature in bacteria. The Escherichia coli Lon protease is involved in the control of the SOS response, acid tolerance and nutritional deprivation. Moreover, Lon plays a role in the regulation of toxin-antitoxin (TA) systems and thereby is linked to persister cell induction. Persister cells represent a small subpopulation that has reversibly switched to a dormant and non-dividing state without genomic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 69 publications
1
44
0
1
Order By: Relevance
“…Also upregulated was the gene coding for cold shock protein D (cspD), which is induced in the stationary phase in an rpoSindependent manner. CspD is responsible for inhibiting replication by binding to single-stranded DNA (ssDNA), and its overexpression is implicated in increased persister cell formation (46). With upregulation of both hipB and cspD, it is possible that there are an increased number of persister cells found in imipenemtreated biofilms, potentially giving insight into the ability of these biofilms to remain viable even with a carbapenem treatment of 1,000ϫ the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Also upregulated was the gene coding for cold shock protein D (cspD), which is induced in the stationary phase in an rpoSindependent manner. CspD is responsible for inhibiting replication by binding to single-stranded DNA (ssDNA), and its overexpression is implicated in increased persister cell formation (46). With upregulation of both hipB and cspD, it is possible that there are an increased number of persister cells found in imipenemtreated biofilms, potentially giving insight into the ability of these biofilms to remain viable even with a carbapenem treatment of 1,000ϫ the MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, conditional proteolysis has only been reported for a few substrates. For instance, (i) increasing temperatures trigger the degradation of the homoserine transsuccinylase HTS (MetA), which catalyzes the first step in the de novo methionine biosynthesis and thereby affects the rate of translation (18), (ii) the stability of the DNA-binding replication inhibitor CspD is adjusted according to the growth rate and growth phase of E. coli cells (19), (iii) anti-sigma factor guided degradation controls the amount of the stationary phase sigma factor RpoS (33), and (iv) the formate dehydrogenase subunit FdoH and the uncharacterized YfgM protein are degraded by FtsH in response to various growth conditions (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although about 15 different FtsH substrates are known, there are many open questions concerning their precise degradation mechanism. Usually, proteolysis of key enzymes or regulatory proteins is not constitutive but tightly controlled to allow adaptation to changing growth conditions (16)(17)(18)(19)(20). Assuming that the stability of LpxC might be coordinated with the cellular demand for LPS under different growth conditions, we set out to monitor LpxC stability at different generation times.…”
mentioning
confidence: 99%
“…MqsR relies on Hha and CspD to form persister cells (39); Hha is a putative toxin with antitoxin TomB (24), and CspD is a stress-induced cold shock protein that is a DNA replication inhibitor (79). Furthermore, since the protease Lon degrades CspD primarily during the stationary phase, it has been hypothesized that degradation of CspD may be related to persister cell awakening (i.e., when growth resumes) (46). Additional findings linking toxin MqsR to persistence include those that mqsR is the most highly induced gene in persister cells compared to nonpersisters (67) and that, in transcriptome studies to probe the impact of kanamycin on cell physiology, mqsRA was found to be one of the most highly induced operons (41).…”
Section: Ta Systems and Biofilm Formationmentioning
confidence: 99%